Jenny Lind's songs. - J.H. Bufford & Co.; Hodson, G. A..; George P. Reed & Co (Boston : Published by Geo. P. Reed : J.H. Bufford's Lith.)
Subject: A portrait of Jenny Lind published about 1848.
Music is titled My Home, My Happy Home" and was composed expressly for Jenny Lind by G.A. Hodson.
Plate 2.
Mode of access: Internet.
From the Thomas A. Edison Collection of American Sheet Music.
Keywords: Lind, Jenny, -- 1820-1887.; Lind, Jenny, -- 1820-1887 -- Portraits; Sheet music covers -- United States -- 1840-1850.; Lithographs -- United States -- 1840-1850.; Portraits